Abandonul şcolar în opt şcoli din mediul urban - Mihalache, Flavius (Calitatea Vieții, 2011)
School dropout is one of the biggest problems of the Romanian educational system after 1990. Dropout rate in Romania is the highest among the member states of the European Union. The first part of the study is dedicated to presenting the main statistical indicators on school population and school dropout in Romania. In the second part of the paper I present the main results of a qualitative research done on school dropout topic in eight urban schools.